A country comparison of place-based activity response to COVID-19 policies. (December 2020) - McKenzie, Grant; Adams, Benjamin
Abstract: The emergence of the novel Coronavirus Disease in late 2019 (COVID-19) and subsequent pandemic led to an immense disruption in the daily lives of almost everyone on the planet. Faced with the consequences of inaction, most national governments responded with policies that restricted the activities conducted by their inhabitants. As schools and businesses shuttered, the mobility of these people decreased. This reduction in mobility, and related activities, was recorded through ubiquitous location-enabled personal mobile devices. Patterns emerged that varied by place-based activity. In this work the differences in these place-based activity patterns are investigated across nations, specifically by focusing on the relationship between government enacted policies and changes in community activity patterns. By addressing five research questions, we show that people's activity response to government action varies widely both across nations as well as regionally within them. Three assessment measures, namely cosine similarity, lag response, and subregional variation, are devised and the results correlate with a number of global indices. We discuss these findings and the relationship between government action and residents' response. Highlights: In response to the emergence of COVID-19, most national governments enacted policies that restricted the activities of their inhabitants. This lead to a reduction in place-based activities which was recorded through location-enabled mobile devices. We investigate the relationship between government enacted policies and changes in community activity patterns, across multiple countries. Our findings indicate substantial differences in response that correlates with a number of global health and development indices.